Proceedings of the 2007 ACM Workshop on Recurring Malcode 2007
DOI: 10.1145/1314389.1314391
|View full text |Cite
|
Sign up to set email alerts
|

A framework for detection and measurement of phishing attacks

Abstract: Phishing is form of identity theft that combines social engineering techniques and sophisticated attack vectors to harvest financial information from unsuspecting consumers. Often a phisher tries to lure her victim into clicking a URL pointing to a rogue page. In this paper, we focus on studying the structure of URLs employed in various phishing attacks. We find that it is often possible to tell whether or not a URL belongs to a phishing attack without requiring any knowledge of the corresponding page data. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
213
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(231 citation statements)
references
References 15 publications
1
213
0
4
Order By: Relevance
“…The work by Garera et al [13] is the most closely related to our work. They use logistic regression over 18 hand-selected features to classify phishing URLs.…”
Section: Machine Learning Approachessupporting
confidence: 60%
“…The work by Garera et al [13] is the most closely related to our work. They use logistic regression over 18 hand-selected features to classify phishing URLs.…”
Section: Machine Learning Approachessupporting
confidence: 60%
“…One camp exploits URL signatures to detect phish. Garera et al [14] identified a set of fine-grained heuristics from URLs, and combined them with other features to detect phish. Applying a logistic regression model on 18 features yielded an average TP of 95.8% and FP of 1.2% over a repository of 2508 URLs.…”
Section: Methods For Automatic Phish Detectionmentioning
confidence: 99%
“…A significant amount of research utilising machine learning algorithms has focused on building efficient detection mechanisms for web and email phishing attacks, with work by Fette et al [2007] and Basnet et al [2008] testing a range of clustering and filtering techniques to classify data for accurate prediction of attack detection. Similarly, the research conducted by Garera et al [2007] highlights the difference between legitimate and illegitimate URLS and proposes a regression filter for constructing classifiers specifically for URL phishing. In a related piece of work, [Bergholz et al 2008] developed a system to detect phishing emails based on the component features of the email, such as body of text, sender address or embedded images, using combinations of machine learning for classification and class modelling mechanisms for filtering.…”
Section: Technicalmentioning
confidence: 99%